Timothy King. Mexico : industrialization and trade policies since 1940. Londres : Oxford University Press, 1970. 151 p. - Trejo Reyes, Saúl (Estudios Demográficos y Urbanos, 1971)
TIMOTHY KING, México: Industrialization and Trade Policies Since 1940, Londres, Oxford University Press, 1970.